PETROGRAPHY AND GEOCHEMISTRY OF CARBONIFEROUS COAL SEAMS IN THE DONETS BASIN (UKRAINE): IMPLICATIONS FOR PALEOECOLOGY - Sachsenhofer R.F.; Sotirov A.; Privalov V.A.; Izart A.; Elie M.; Kortensky J.; Panova E.A.; Zhykalyak M.V. (My University, 2003)
The Carboniferous succession in the Donets Basin hosts about 130 seams, each with a thickness over 0.45 m. Nine economically important seams from the (south)western Donets Basin are studied using organic petrographical, inorganic geochemical, and organic geochemical techniques. The main aim of the study is the reconstruction of peat facies of Serpukhovian (Mississippian) and Moscovian (Middle Pennsylvanian) coals.Formation of major coal seams commenced during Serpukhovian times. Early Serpukhovian coal accumulated in a relatively narrow shore-zone and is rich in inertinite and liptinite. Very low ash yields, low to moderate sulphur contents, and upward increasing inertinite contents suggest coal deposition in raised mires.Moscovian coal has a significantly wider lateral extension and is generally rich in vitrinite. Coal properties vary widely in response to different peat facies. Low-sulphur, low-ash k7 coal was formed in a raised mire or in a low-lying mire without detrital input. l1 and l3 seams containing several fluvial partings were formed in low-lying mires. Both seams are more than 2 m thick. Seams m2 and m3 contain high-sulphur coal, a consequence of deposition in a peat with marine influence. In contrast, syngenetic sulphur content is low in the m51 upper seam, which was formed in a lacustrine setting. The late Moscovian n1 seam, up to 2.4 m thick, accumulated in a swamp with a vegetation rich in bryophytes and pteridophytes. The properties of the n1 seam are transitional between those of Serpukhovian and other Moscovian seams. Differences in maceral composition between Serpukhovian and Moscovian coals probably reflect changes in climate and vegetation type.Tuff layers are observed in the l1, l3, and m3 seams. The l3 and m3 seams contain abundant authigenic quartz. Trace element contents are high in many seams. As contents are especially high in seams c102, k7, l3 and m3. Ash in the l3 seam contains up to 8000 ppm As. Co is enriched near the base of several seams. Maxima up to 2400 ppm occur in the ash of the k7 and l3 seams. Cd contents in ash are frequently as high as 30 or 40 ppm.
Keywords: Ukraine; Coal; Serpukhovian; Moscovian; Organic geochemistry; Inorganic geochemistry; Coal petrography; Paleozoic::Carboniferous; Палеозой::Каменноугольная